2010
DOI: 10.1186/cc8961
|View full text |Cite
|
Sign up to set email alerts
|

Low hemoglobin is associated with poor functional outcome after non-traumatic, supratentorial intracerebral hemorrhage

Abstract: IntroductionThe impact of anemia on functional outcome and mortality in patients suffering from non-traumatic intracerebral hemorrhage (ICH) has not been investigated. Here, we assessed the relationship between hemoglobin (HB) levels and clinical outcome after ICH.MethodsOne hundred and ninety six patients suffering from supratentorial, non-traumatic ICH were extracted from our local stroke database (June 2004 to June 2006). Clinical and radiologic computed tomography data, HB levels on admission, mean HB valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 37 publications
4
71
2
3
Order By: Relevance
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…There were also 2 studies that did not state the design 21, 26. There was a high degree of diversity in geographic location, with cohorts from Germany,8, 19, 25 Switzerland,16, 20 the United States,18, 24 the People's Republic of China,2, 22 Canada,23, 28 India,6 Israel,10 the Republic of Korea,9 Denmark,21 Taiwan,17 the United Kingdom,26 and Poland 7. In addition, 2 studies were conducted across multiple countries 1, 27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations